2018
DOI: 10.3390/app8010048
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of Classifying the Causes of Occupational Accidents Involving Construction Scaffolding Using Pareto-Lorenz Analysis

Abstract: This article presents the developed methodology of classifying and evaluating the causes of accidents involving construction scaffolding. This methodology allows the causes of accidents to be identified, classified into generic groups, and also allows the importance of individual causes in their generic groups to be assessed. For the classification of causes, the Technical-Organizational-Human (TOH) method was used. Its assumption is the division of causes into technical (T), organizational (O), and human (H) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…• analysis of the mechanisms of the occurrence of occupational accidents [1,2], • analysis of the causes of accidents at work [3][4][5], • identi cation of direct and indirect factors which affect the accident rate [6][7][8] • analysis of the accident rate with regards to factors that generate costs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…• analysis of the mechanisms of the occurrence of occupational accidents [1,2], • analysis of the causes of accidents at work [3][4][5], • identi cation of direct and indirect factors which affect the accident rate [6][7][8] • analysis of the accident rate with regards to factors that generate costs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Before the Pareto-Lorenz diagram was made it was necessary to prepare data regarding the incompatibilities (Hoła et. al., 2017;Hola et. al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The identification and analysis of accident factors is an important area of scientific research, as it is the basis for the proper design and planning of training and preventive actions, which in turn leads to reduced accidents at work [10,[12][13][14][15][16][17].…”
Section: Literature Surveymentioning
confidence: 99%
“…The author, based on an analysis of the subject literature, made a detailed classification of accident factors, and then divided them into four main groups related to: working conditions, employees, management and organization of work, as well as work environment. Moreover, studies [17] in which the authors proposed a methodology for the classification of direct causes of accidents on scaffolding are also interesting. Using Pareto-Lorenzo analysis, the authors of the research identified causes that have the greatest impact on the occurrence of accidents.…”
Section: Literature Surveymentioning
confidence: 99%